A Mediterranean Diet Rich in Extra-Virgin Olive Oil Is Associated with a Reduced Prevalence of Nonalcoholic Fatty Liver Disease in Older Individuals at High Cardiovascular Risk. Issue 11 (23rd July 2019) - Pintó, Xavier; Fanlo-Maresma, Marta; Corbella, Emili; Corbella, Xavier; Mitjavila, M Teresa; Moreno, Juan J; Casas, Rosa; Estruch, Ramon; Corella, Dolores; Bulló, Mònica; Ruiz-Canela, Miguel; Castañer, Olga; et al.
ABSTRACT: Background: Adherence to a Mediterranean diet (MedDiet) is thought to reduce liver steatosis. Objectives: To explore the associations with liver steatosis of 3 different diets: a MedDiet + extra-virgin olive oil (EVOO), MedDiet + nuts, or a control diet. Methods: This was a subgroup analysis nested within a multicenter, randomized, parallel-group clinical trial, PREvención con DIeta MEDiterránea (PREDIMED trial: ISRCTN35739639), aimed at assessing the effect of a MedDiet on the primary prevention of cardiovascular disease. One hundred men and women (mean age: 64 ± 6 y), at high cardiovascular risk (62% with type 2 diabetes) from the Bellvitge-PREDIMED center were randomly assigned to a MedDiet supplemented with EVOO, a MedDiet supplemented with mixed nuts, or a control diet (advice to reduce all dietary fat). No recommendations to lose weight or increase physical activity were given. Main measurements were the percentage of liver fat and the diagnosis of steatosis, which were determined by NMR imaging. The association of diet with liver fat content was analyzed by bivariate analysis after a median follow-up of 3 y. Results: Baseline adiposity and cardiometabolic risk factors were similar among the 3 treatment arms. At 3 y after the intervention hepatic steatosis was present in 3 (8.8%), 12 (33.3%), and 10 (33.3%) of the participants in the MedDiet + EVOO, MedDiet + nuts, and control diet groups, respectively ( P = 0.027). Respective mean values of liver fat content were 1.2%, 2.7%, and 4.1% ( P = 0.07). A tendency toward significance was observed for the MedDiet + EVOO group compared with the control group. Median values of urinary 12( S )-hydroxyeicosatetraenoic acid/creatinine concentrations were significantly ( P = 0.001) lower in the MedDiet + EVOO (2.3 ng/mg) than in the MedDiet + nuts (5.0 ng/mg) and control (3.9 ng/mg) groups. No differences in adiposity or glycemic control changes were seen between groups. Conclusions: An energy-unrestricted MedDiet supplemented with EVOO, a food with potent antioxidant and anti-inflammatory properties, is associated with a reduced prevalence of hepatic steatosis in older individuals at high cardiovascular risk.